A programmable lipid-polymer hybrid nanoparticle system for localized, sustained antibiotic delivery to Gram-positive and Gram-negative bacterial biofilms. Issue 3 (8th February 2018) - Baek, Jong-Suep; Tan, Chuan Hao; Ng, Noele Kai Jing; Yeo, Yee Phan; Rice, Scott A.; Loo, Say Chye Joachim
Abstract : Lipid-polymer hybrid nanoparticle enhances antibiotic efficacy through localised, sustained delivery to bacterial biofilms. Abstract : Bacteria enmeshed in an extracellular matrix, biofilms, exhibit enhanced antibiotic tolerance. Coupled with the rapid emergence of multidrug-resistant strains, the current cohorts of antibiotics are becoming ineffective. Alternative antimicrobial approaches are therefore urgently needed to overcome recalcitrant biofilm infections. Here, we propose the use of a non-toxic lipid-polymer hybrid nanoparticle (LPN) system composed of a solid polymer core ( i.e. PLGA; poly lactic- co -glycolic acid) and a cationic lipid shell ( i.e. DOTAP) for localized, sustained release of antimicrobial agents to bacterial biofilms. LPNs were synthesized through a simple, robust self-assembly approach. LPNs of uniform particle size ( i.e. 100–130 nm), efficiently encapsulated (up to 95%) bioimaging molecules or antibiotics and provided controlled release of the latter. The cationic lipid coating enabled the LPN to anchor onto surfaces of a diverse range of Gram-positive and Gram-negative bacterial pathogens, either in the planktonic or biofilm form. Consistently, the LPN formulations reduced more than 95% of biofilm activity at concentrations that were 8 to 32-fold lower than free antibiotics. These data clearly indicate that these novel formulations could be a useful strategy to enhance the efficacy of antimicrobials against planktonic cells and biofilms of diverse species.